Penanggulangan Tindak Pidana Pemerasan di Wilayah Hukum Kepolisian Sektor Pelayangan Kota Jambi - Hartono, M. Rudi; Akbar, Hikmal (Wajah Hukum, 2026)
Criminal behavior in society takes many forms, one of which is extortion. In general, extortion involves the act of demanding something by force, either through violence or threats. This includes forcing someone to hand over their belongings in whole or in part, or to accumulate debt or write off receivables, with the intention of benefiting oneself or others at the expense of their rights. The coercive aspect of extortion usually involves the use of violence or violent intimidation. The legal framework governing extortion was regulated in Article 368 of the Criminal Code before the enactment of Law Number 1 of 2023, which established the new Criminal Code. Extortion in a society can result in various losses, including material and non-material losses. Furthermore, this criminal act can endanger the safety of individuals. Eradicating crime is a logical effort by officials and members of society to address this problem and promote shared prosperity. Therefore, preventive measures are crucial to prevent criminal activity, especially related to the extortion crime examined in this study, which is related to the Jambi City Police Service Sector. This study employs an empirical legal methodology, utilizing a socio-legal approach. Data for this study comes from fieldwork, which involves direct information collection through observation or investigation. The findings of this study indicate factors contributing to the prevalence of extortion crimes within the Jambi City police jurisdiction. These factors include economic factors, such as the perpetrators' lack of employment and steady income; environmental factors, such as the influence of their surroundings; and personality factors, such as laziness to find work and supplement their income; a lack of faith; a lack of sound decision-making ability; and a thuggish nature.